Utilization Of Guava Leaves Extract (Psidium Guajava) As Ecofriendly Corrosion Inhibitor For Iron - Akbar, Said Ali; Ovisa, Rika; Muttakin, Muttakin (Al-Kimia, 2019)
The use of a green inhibitor from guava leaves extract as an alternative to environmentally friendly metal corrosion inhibitors has been carried out. The guava leaves extracted by 96% ethanol in the maserator for 4 days with occasional shaking and two rejuvenations. The inhibitor performance test was carried out using 2 types of water (wells and sea), as well as variations in extract concentrations of 3%, 10% and 25%. Through phytochemical testing results, it was found that the active secondary metabolite components contained in guava leaves are flavonoids, terpenoids, and tannins. Increasing the concentration of guava leaves extract in well and sea water samples, reducing the value of the corrosion rate. In seawater, the use of 25% leaves extract, there was a weight increase of nails only 0.165% of the initial weight compared with no extract which was 10.75% of the initial weight. Furthermore, the greatest inhibitor efficiency occurred at 25% extract concentration, which was 96.39% in well water media and 97.07% in sea water media. Therefore, guava leaves have the potential to be used as future green inhibitor applications.